"Psychological Effects of Parental Remigration on Young School-Age Pupils From A Social And Educational Point Of View" - Emilia Bidică; Horațiu Catalano (Babes-Bolyai University, 2023)
The adaptation of modern man to the demands of globalization, to economic and social needs, has led to the accentuation of some social phenomena (migration and remigration) in terms of the exodus of part of the population. The latter are seeking economic and social stability for their families. Migration is a sensitive issue of interest to both countries of origin and destination. Remigration of Romanian citizens is a phenomenon that produces more or less predictable social, educational, economic and, especially, individual effects. Many migrants do not achieve their goals, many have negative experiences of migration so that their physical and mental state is affected, but even more return home disillusioned and sometimes traumatized by this experience, many of them being children. The phenomenon of remigration (returning to the country of origin after a failed migration experience) has a strong impact on the well-being and development of the student. The social and school adaptation of the pupil and his/her reintegration into social activities presents, in most cases, major difficulties: low self-esteem, school failure, hyperactivity/attention deficit, social isolation.